OPTIMIZATION OF WATER SUPPLY UTILIZATION FOR IRRIGATION WATER DEMAND ON WALUH RIVER (LOCATION PEMALANG REGENCY CENTRAL JAVA PROVINCE) - ISKANDAR (NIM : 95014306), YUDI
Waluh River located in Pemalang Regency Central Java Province has been used to meet the water needs of several irrigation areas, among others from upstream to downstream: DI. Kejene (476.75 Ha), DI. Glandang (123.00 Ha), DI. Lanjiladang (788.69 Ha), DI. Sulang (50.00 Ha), DI. Lenggerong (41.00 Ha) and DI. Sungapan (7,085.55 Ha). The Waluh River also supplies water to the Sungai Rambut for DI. Rambut 20% of water availability at DI. Kejene. Irrigated areas with the lowest downstream position are likely to experience water shortage if no optimal planting schedule is set in each irrigation area from upstream to downstream. In order to obtain an optimal cropping schedule in each irrigation area, five alternative planting schedule plans were made: alternatively 1 MT-I schedule commenced in September I, alternatively 2 MT-I schedules starting September 2, alternate 3 MT-I schedules starting October- I, alternate 4 MT-I schedules started in October II and alternatively 5 MT-I schedules started in November I. Furthermore, optimal cropping schedule is chosen in accordance with water availability, irrigation water demand and water requirement for river maintenance. The method used to determine the optimal cropping schedule is to use the Dynamic Program Method. Current cropping schedule DI. Kejene MT-I schedule starts in November I, DI. Glandang MT-I schedule starts in November I, DI. Lanjiladang MT-I schedule starts in November I, DI. Sulang MT-I schedule starts in November I, DI. Lenggerong MT-I schedule starts in November I and DI. Sungapan MT-I schedule starts in October I. According to the availability of water by applying the planting schedule is obtained rice planting area 12,168.00 Ha and corn 854.27 Ha. The result of determining the cropping schedule by using the Dynamic Program method, obtained the optimal planting schedule as follows: DI. Kejene MT-I schedule starts in October-II, DI. Glandang MT-I schedule starts in October-II, DI. Lanjiladang MT-I schedule starts in October-II, DI. Sulang MT-I schedule starts in October II, DI. Lenggerong MT-I schedule starts in October II and DI. Sungapan MT-I starts in November I. By applying these planting schedule then retrieved, rice planting area of 12,788.86 Ha, crop palawija 359.58 Ha, with total farming income of Rp. 150,916,305,000.00 per year.